Tissue Degeneration following Loss of Schistosoma mansoni cbp1 Is Associated with Increased Stem Cell Proliferation and Parasite Death In Vivo. - Julie N R Collins (PLoS Pathogens, 2016)
Schistosomiasis is second only to malaria in terms of the global impact among diseases caused by parasites. A striking feature of schistosomes are their ability to thrive in their hosts for decades. We have previously demonstrated that stem cells, called neoblasts, promote homeostatic tissue maintenance in adult schistosomes and suggested these cells likely contribute to parasite longevity. Whether these schistosome neoblasts have functions independent of homeostatic tissue maintenance, for example in processes such as tissue regeneration following injury, remains unexplored. Here we characterize the schistosome CBP/p300 homolog, Sm-cbp1. We found that depleting cbp1 transcript levels with RNA interference (RNAi) resulted in increased neoblast proliferation and cell death, eventually leading to organ degeneration. Based on these observations we speculated this increased rate of neoblast proliferation may be a response to mitigate tissue damage due to increased cell death. Therefore, we tested if mechanical injury was sufficient to stimulate neoblast proliferation. We found that mechanical injury induced both cell death and neoblast proliferation at wound sites, suggesting that schistosome neoblasts are capable of mounting proliferative responses to injury. Furthermore, we observed that the health of cbp1(RNAi) parasites progressively declined during the course of our in vitro experiments. To determine the fate of cbp1(RNAi) parasites in the context of a mammalian host, we coupled RNAi with an established technique to transplant schistosomes into the mesenteric veins of uninfected mice. We found transplanted cbp1(RNAi) parasites were cleared from vasculature of recipient mice and were incapable of inducing measurable pathology in their recipient hosts. Together our data suggest that injury is sufficient to induce neoblast proliferation and that cbp1 is essential for parasite survival in vivo. These studies present a new methodology to study schistosome gene function in vivo and highlight a potential role for schistosome neoblasts in promoting tissue repair following injury.